Can the NHSN dialysis event protocol be implemented in an Irish dialysis unit? - Bajwa, Raazi; Casey, Anne; Collier, Cathail; O’Kelly, Patrick; Conlon, Peter; Fitzpatrick, Fidelma (International Journal of Infection Control, 2012)
Infection is the second most common cause of death in patients with chronic kidney disease and so International guidelines recommend surveillance of infection in dialysis units. This study examines the feasibility of establishing and maintaining the National Healthcare Safety Network (NSHN) dialysis event protocol in our hospital. Two outpatient haemodialysis wards were surveyed for six weeks using the NHSN dialysis events protocol. Numerator data were collected by recording dialysis events; hospitalisation, intravenous (IV) antimicrobial start or a positive blood culture. Hospitalisations, IV antimicrobial starts and positive blood cultures were recorded at rates of 13, 8.52 and 3.14 per 100 patient months, respectively. Seven vascular access infections; six access associated bacteraemias and one complication (infective endocarditis) were recorded. Dialysis events were more common in patient with IV catheters when compared with patients with fistulas (p<0.001). The rate of IV antimicrobial starts was significantly higher than NHSN rates (p=0.001). NHSN surveillance protocol use allows the establishment of standardised baseline dialysis event rates and has highlighted antimicrobial use and higher event rates in patients with IV catheters as areas for improvement. On-going surveillance is feasible, though dependent on multidisciplinary dialysis staff involvement & ownership and the presence of a surveillance coordinator.